Edició i estudi d'alguns poemes catalans en un manuscrit de don Francesc de la Torre i Sebil - Brown, Kenneth; Escartí, Vicent J. (Caplletra. Revista Internacional de Filologia, 2015)
The work of Francesc de la Torre is positioned in the baroque context, in the junction between linguistic conflict and literary language configuration. Kenneth Brown and Vicent Escartí edit ten unpublished Catalan poems of this author included in a miscellany manuscript. A brief study of the literary atmosphere and the significance of these texts is included.